Episcopal networks in late antiquity connection and communication across boundaries - Cvetković, Carmen Angela 19XX-; Gemeinhardt, Peter 1970- (Berlin Boston De Gruyter, 2019)
Frontmatter -- Table of Contents -- Abbreviations -- Introduction -- Part 1: The Ties That Bind -- Episcopal Nepotism in the Later Roman Empire (c. 350–450) / Menze, Volker -- A New Approach to Ambrose of Milan’s Kinship / Bodin, Ariane -- Influential Friends? Augustine’s Episcopal Networks / Clark, Gillian -- The Authority of a ‘Quasi-Bishop:’ Patronage and Networks in the Letters of Isidore of Pelusium / Toca, Madalina / Leemans, Johan -- Patronage Networks in the Festal Letters of Athanasius of Alexandria / Gwynn, David M. -- Bishops as Religious Mentors: Spiritual Education and Pastoral Care / Gemeinhardt, Peter -- Crossing the Boundaries: Networks and Manifestations of Christian Hospitality / Mratschek, Sigrid -- Niceta of Remesiana’s Visits to Nola: Between Sacred Travel and Political Mission / Cvetković, Carmen Angela -- Part 2: Episcopal Networks in Context -- The Impact of the Laurentian Schism on Ennodius of Pavia’s Participation in Episcopal Networks / Knox, Daniel K. -- Building and Breaking Episcopal Networks in Late Antique Hispania / Wood, Jamie -- Macedonius, Constantius and the Changing Dynamics of Power / Manders, Erika -- Caring for African Confessors in Exile: The Ministry of Numeria and Candida during the Decian Persecution (Cyprian, Epistulae 21–22) / Engberg, Jakob -- The Impact of Geographical and Administrative Boundaries on Late Antique Bishops / Slootjes, Daniëlle -- Bishops and Mission Beyond the Frontiers: From Gothia to Nubia / Sterk, Andrea -- List of Contributors -- Index of Authors and Texts -- Index of Ancient Places -- Index of Modern Authors
Recent studies on the development of early Christianity emphasize the fragmentation of the late ancient world while paying less attention to a distinctive feature of the Christianity of this time which is its inter-connectivity. Both local and trans-regional networks of interaction contributed to the expansion of Christianity in this age of fragmentation. This volume investigates a specific aspect of this inter-connectivity in the area of the Mediterranean by focusing on the formation and operation of episcopal networks. The rise of the bishop as a major figure of authority resulted in an increase in long-distance communication among church elites coming from different geographical areas and belonging to distinct ecclesiastical and theological traditions. Locally, the bishops in their roles as teachers, defenders of faith, patrons etc. were expected to interact with individuals of diverse social background who formed their congregations and with secular authorities. Consequently, this volume explores the nature and quality of various types of episcopal relationships in Late Antiquity attempting to understand how they were established, cultivated and put to use across cultural, linguistic, social and geographical boundaries
Literaturangaben
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: RELIGION / Christian Church / History; Bishops; Late Ancient Christianity; communication; social networks; Aufsatzsammlung